UMPSA aims for 3 gold medals at SUKIPT 2024 - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 30 August 2024 – The Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Ts. Dato' Dr. Yuserrie Zainuddin, recently handed over the UMPSA flag to the contingent representative, Ahmad Azad Rifqi Redzuan, who will represent the university at the 2024 Higher Education Institution Games (SUKIPT) in Sintok, Kedah.